Singlet oxygen imaging using fluorescent probe Singlet Oxygen Sensor Green in photosynthetic organisms - Prasad, Ankush; Sedlářová, Michaela; Pospíšil, Pavel (Scientific reports, 2018)
Formation of singlet oxygen (1O2) was reported to accompany light stress in plants, contributing to cell signaling or oxidative damage. So far, Singlet Oxygen Sensor Green (SOSG) has been the only commercialized fluorescent probe for 1O2 imaging though it suffers from several limitations (unequal penetration and photosensitization) that need to be carefully considered to avoid misinterpretation of the analysed data. Herein, we present results of a comprehensive study focused on the appropriateness of SOSG for 1O2 imaging in three model photosynthetic organisms, unicellular cyanobacteria Synechocystis sp. PCC 6803, unicellular green alga Chlamydomonas reinhardtii and higher plant Arabidopsis thaliana. Penetration of SOSG differs in both unicellular organisms; while it is rather convenient for Chlamydomonas it is restricted by the presence of mucoid sheath of Synechocystis, which penetrability might be improved by mild heating. In Arabidopsis, SOSG penetration is limited due to tissue complexity which can be increased by pressure infiltration using a shut syringe. Photosensitization of SOSG and SOSG endoperoxide formed by its interaction with 1O2 might be prevented by illumination of samples by a red light. When measured under controlled conditions given above, SOSG might serve as specific probe for detection of intracellular 1O2 formation in photosynthetic organisms.
Keywords: Photosynthesis; fluorescenční barviva; světlo; singletový kyslík; oxidace-redukce; Chlamydomonas reinhardtii; Fluorescent Dyes; Singlet Oxygen; Oxygen; Color; kyslík; Light; Oxidation-Reduction; fotosyntéza; Arabidopsis; barva